Formulation and In-Vitro Evaluation of Fast Dissolving Oral Films of Promethazine - Chaudhari, Pradyumna; Maurya, Rohit; Lamsal, Ashish; Thapa, Shankar (Journal of Universal College of Medical Sciences, 2023)
INTRODUCTION Fast disintegrating/dissolving medicine delivery devices are oral ﬁlms that swiftly disintegrate or adhere in the mouth. It includes the ability to administer systemic medications without having any ﬁrst-pass effects. A ﬁrst-generation antihistamine from the phenothiazine family is promethazine HCl. It is effective in treating motion sickness but it has a poor oral bioavailability. The study aims is to formulate promethazine fast dissolving oral ﬁlm using natural and synthetic polymers and compare the formulations. MATERIAL AND METHODS This experimental study was conducted in the Pharmaceutic laboratory of Department of Pharmacy at Universal College of Medical Sciences, Bhairahawa, Nepal from February 2022 to July 2022. Fast dissolving oral ﬁlms of promethazine were prepared by solvent casting method using polymers and plasticizers in varying concentrations. Weight variation, thickness variation, surface pH, folding endurance, swelling index, disintegration duration, dissolution study and medication content were among the several in vitro assessment criteria that were identiﬁed. RESULTS When examined for physical characteristics, thickness, weight uniformity, in vitro disintegration time, folding durability, drug content, and an in vitro drug release, ﬁlms were determined to be adequate. The ﬁlms of the F2 formulation demonstrated an increased rate of drug dissolution with a drug content of 99.17%, a disintegration time of 38 sec, and a drug release of more than 99% within 16 min. CONCLUSION Synthetic polymer (Hydroxypropyl methyl cellulose) showed better result in comparison to natural polymer (Sodium alginate).